A study of the effects of heartwater and its control on livestock productivity and economics in Zimbabwe - Perry, Brian D.; Chamboko, Tafireyi; Mahan, S.; Medley, G.F.; Mukhebi, A.W.; O'Callaghan, C.J.; Peter, T.F. (1997)
Heartwater, a disease of ruminants caused by the rickettsia Cowdria ruminantium and transmitted by ticks of the genus Amblyomma, is a significant cause of productivity losses in cattle, sheep and goats in most of sub-Saharan Africa. In southern Africa, the vector of C. ruminantium is A. hebraeum. In most of the rest of the continent, the main vector is A. variegatum, and it is in Zimbabwe that the distributions of these two vectors now overlap. In Zimbabwe, the disease has historically been confined to the southern lowveld of the country, but in recent years, this situation has changed as A. hebraeum has spread north. The disease has been prevented and controlled by the intensive use of acaricides, which have provided the mainstay for the control of this and other tick-borne diseases, such as theileriosis, babesiosis and anaplasmosis, for decades. The USAID supported heartwater research project of the University of Florida and the southern Africa Development Community (SADC) has been working on improved technologies for the control of the disease, in particular through the use of an inactivated tissue culture vaccine (Mahan, et al 1995). This vaccine has demonstrated high levels of efficacy in clinical trials, and is presently undergoing evaluation on a wider scale in the SADC region. In addition to vaccine Development, the project is studying the epidemiology of heartwater in Zimbabwe, the impact of the disease on productivity and the economic merits of future vaccine-based control strategies, in work co-ordinated by the International Livestock Research Institute (ILRI). An overview of the current progress in these studies is provided in this paper.